Anthropometry and biomechanics: characteristics, principles and anthropometric models - Saray Giovana dos Santos; Sebastião Iberes Lopes Melo (Universidade Federal de Santa Catarina, 2000)
Due to the importance of interdisciplinarity and multidisciplinarity to the complex analysis of human movement, and in an attempt to seek to bring Kinanthropometry and Biomechanics closer together, throughanthropometry, this review article was compiled in order to: present the historical evolution of anthropometry and the theoretical presuppositions on which its anthropometric models are based; to present anthropometry as a method for measurement in biomechanics; to describe the role and scope of anthropometry in biomechanics by discussing some of its applications and contributions. Initially, an analysis is made of historical and conceptual aspects and anthropometric models are presented and characterized together with their theoretical presuppositions and limitations. Anthropometry is then analyzed in the context of the different methods for measuring in biomechanics, studying its position within the process of analyzing human movement as a prerequisite of kinemetry and dynamometry and also of synchronized analysis. What follows is a reﬂ ection on the role and scope of anthropometry within the analysis of movement, with examples from drawn from several studies, and an identiﬁ cation of their respective contributions. Finally, some considerations resulting from this reﬂ ection are presented; the degree of development of anthropometric models is identiﬁ ed and the constant pursuit for improvement over recent years, with the use of ever more sophisticated techniques, is demonstrated. RESUMO Face à importância da inter e da multidisciplinariedade na complexa análise do movimento humano e no intuito de buscar a aproximação da Cineantropometria e da Biomecânica, através da antropometria, realizou-se este estudo de revisão com o objetivo de apresentar a evolução histórica da antropometria e os pressupostos teóricos de seus modelos antropométricos; apresentar a antropometria enquanto método de medição em biomecânica; descrever o papel e o alcance da antropometria na biomecânica comentando algumas aplicações e suas contribuições. Inicialmente se faz uma abordagem dos aspectos históricos, conceituais e são apresentados os modelos antropométricos caracterizando-os e apresentando seus pressupostos teóricos e limitações; num segundo momento a antropometria é analisada no contexto dos diferentes métodos de medição em biomecânica, estudando sua insersão no processo de análise do movimento humano tanto como pré-requisito da cinemetria e da dinamometria como na análise sincronizada. Segue então, uma reﬂ exão sobre o papel e o alcance da antropometria na análise do movimento, exempliﬁ cando-os com diferentes estudos e identiﬁ cando suas respectivas contribuições; por ﬁ m são apresentadas algumas considerações resultantes desta reﬂ exão, onde se constata o estágio de desenvolvimento dos modelos antropométricos e a busca constante do aprimoramento nos últimos anos, utilizando-se técnicas cada vez mais soﬁ sticadas.